NEUROPROTECTIVE POTENTIAL OF CARICA PAPAYA SEED EXTRACT AGAINST OKADAIC ACID-INDUCED MEMORY IMPAIRMENT IN A ZEBRAFISH MODEL OF ALZHEIMER’S DISEASE - Arjun Singh Tyagi; Kokkula Pavan Kumar; Seema Tomar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Alzheimer’s disease (AD) represents a chronic, progressive neurodegenerative disorder characterized by cognitive deterioration, synaptic dysfunction, and neuronal degeneration, ultimately resulting in memory impairment and compromised daily functioning. Given that current therapeutic approaches provide only symptomatic relief, there is growing interest in investigating natural compounds for their neuroprotective capabilities. This research evaluated the protective effects of ethanolic extract derived from Carica papaya seeds against AD-like symptoms in a zebrafish model. In this model, neurotoxicity and memory impairment were induced using Okadaic acid, a compound known to replicate key AD pathological features including cholinergic deficits and tau hyperphosphorylation.The study employed Behavioural assessments, specifically the T-maze and light/dark preference tests, to evaluate cognitive function and anxiety-related Behaviours. Additionally, biochemical analysis of acetylcholinesterase (AChE) activity and histopathological examination of brain tissues were conducted to assess the extract’s effects at molecular and cellular levels. Treatment with C. papaya seed extract at a dosage of 100 mg/kg significantly enhanced Behavioural outcomes, decreased AChE activity, and maintained neuronal structure integrity compared to the Okadaic acid-treated control group.These results suggest that Carica papaya seed extract shows promise as a natural therapeutic agent for neurodegenerative conditions such as AD. The potential mechanisms may involve modulation of the cholinergic system and preservation of neuronal integrity, warranting further investigation through comprehensive mechanistic and clinical studies.